Benign Prostatic Hyperplasia: A New Metabolic Disease of the Aging Male and Its Correlation with Sexual Dysfunctions - Giovanni Corona; Linda Vignozzi; Giulia Rastrelli; Francesco Lotti; Sarah Cipriani; Mario Maggi (International Journal of Endocrinology)
Metabolic syndrome (MetS) is a well-recognized cluster of cardiovascular (CV) risk factors including obesity, hypertension, dyslipidemia, and hyperglycaemia, closely associated with an increased risk of forthcoming cardiovascular disease and type 2 diabetes mellitus. Emerging evidence indicates that benign prostate hyperplasia (BPH) and its related lower urinary tract symptoms (LUTS) represent other clinical conditions frequently observed in subjects with MetS. Several modifiable factors involved in MetS determinism, such as inadequate diet, lack of physical exercise, and smoking and drinking behaviours are emerging as main contributors to the development of BPH. The pathogenetic mechanisms underlying the connection between MetS and BPH have not been completely clarified. MetS and its components, hypogonadism, and prostate inflammation probably play an important role in inducing BPH/LUTS. Although historically considered as a “normal” consequence of the aging process, BPH/LUTS should now be faced proactively, as a preventable disorder of the elderly. Type of diet and level of physical activity are now considered important factors affecting prostate health in the aging male. However, whether physical exercise, weight loss, and modifications of dietary habit can really alter the natural history of BPH/LUTS remains to be determined. Further research is advisable to better clarify these points.